Investing in Our Young People - Cunha, Flavio
This paper reviews the recent literature on the production of skills of young persons. The literature features the multiplicity of skills that explain success in a variety of life outcomes. Noncognitive skills play a fundamental role in successful lives. The dynamics of skill formation reveal the interplay of cognitive and noncognitive skills, and the presence of critical and sensitive periods in the life-cycle. We discuss the optimal timing of investment over the life-cycle.skill formation, cognitive skills, noncognitive skills, technology of skill formation, investment in children